Análisis del clima laboral en la empresa textil Cristal Design, Ibarra-Imbabura - Murillo Arteaga, Vanessa Irene (2023)
The objective of this study is to analyze the work environment in the Cristal Design Textile Company, which is affected by some negative factors that have caused the rupture of the work environment. The research began with bibliographic and field studies that have helped to complement the information collected through the interview applied to twenty-eight employees of the company, where variables that are affecting the work environment have been detected, which are reflected in performance and productivity. Its application was supported by statistical techniques that allowed us to see the feasibility and reliability of the data, and their interpretation. The research focused on analyzing, detecting and seeking effective solutions that help improve and strengthen the weak points found. With the results obtained, an improvement plan is proposed whose purpose is to transform the negative aspects into positive ones that affect the work environment and increase employee satisfaction so that they are more productive. Finally, for each proposed chapter, conclusions and recommendations are presented, considered as a contribution for the execution or start-up of this work environment study